Covid 19 occupational or environmental hazard or both? - Kiran Kumar N., Dr.; Savitha B Naik, Dr.; Laxmi Priya C. H., Dr.; Pavithra Prabakara, Dr.; Annapoorna B. S., Dr.; Arun Kumar R. V., Dr. (International Journal of Dental Research, 2021)
Covid -19 has taken a huge toll on health care sector. Many health care workers (HCWs) fall susceptible to this pandemic infection leading to occupational health hazard. It also has significantly changed the practice of dentistry. Importance of personal protective equipment cannot be enough stressed upon in present scenario due to uncertainity of vaccine availability and efficacy. Major role in protection of health care workers is played by face masks and respirators. Due to crisis in present scenario, there has been an acute shortage of masks though the production has been upregulated. Also due to increased production of masks, it has posed a significant environmental hazard. This review aims to summarize different types of masks available, their effectiveness and optimization of usage of masks to derive adequate protection thus preventing occupational health hazard with emphasis on eco-friendly masks for a better environmental safety.Â Â Â